With dual training in the world of work : learning by working - Szilágyi, János [Herausgeber]; Modláné Görgényi, Ildikó [Verfasser] (My University, 2015)
"For the past 25 years, vocational education and training in Hungary has undergone significant changes. Following the initial period of discovering the right development path after the transition, events took up speed in the past five-six years and resulted in a modern, dual VET system. It is based on the German model and has been established in accordance with Hungarian demands. The reform-like transformation process started in 2010. The peak of this period was in 2012-2013, when following the preparatory of the previous years the new system was launched and prevailed. This publication reviews and summarizes the development process and the milestones of establishing of the system, as well as presents its operation and peculiarities." (Excerpt, BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.2.2 Osteuropa; Berufsbildungssystem; Berufsbildung; Reform; Duales System; Ungarn